1994
DOI: 10.2527/1994.7251107x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of live and carcass equations predicting percentage of cutability, retail product weight, and trimmable fat in beef cattle3

Abstract: Forty-four Hereford-sired steers were measured ultrasonically for backfat and longissimus muscle area between the 12th and 13th ribs before slaughter and visually appraised for fatness, overall muscling, and frame. Carcass measurements associated with USDA yield and quality grades were measured and recorded. Carcasses were fabricated into closely trimmed, boneless subprimals at 1.27- and .32-cm fat trim levels. Cutability percentage (percentage of retail cuts from the cold carcass weight) and kilograms of reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
91
8
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(131 citation statements)
references
References 0 publications
19
91
8
13
Order By: Relevance
“…Negative correlations between live animal muscular scores taken preslaughter and carcass bone proportion were obtained by MacAodhá in (2004) (1980) found that animals in convex hind-quarter (heavy muscled) classes had more muscle and a higher muscle-to-bone ratio than those in concave classes. The positive relationship between pre-slaughter muscular scores and the proportion of high-value cuts in the carcass (r 5 0.31) was higher than that obtained by Herring et al (1994) using eight cuts from the carcass compared with three cuts in the present study. The lack of a relationship between live animal muscular scores and the proportion of high-value cuts in meat indicates that, when bone and fat are excluded, there is no effect of muscular score on the distribution of meat in the carcass.…”
Section: Assessorscontrasting
confidence: 80%
See 2 more Smart Citations
“…Negative correlations between live animal muscular scores taken preslaughter and carcass bone proportion were obtained by MacAodhá in (2004) (1980) found that animals in convex hind-quarter (heavy muscled) classes had more muscle and a higher muscle-to-bone ratio than those in concave classes. The positive relationship between pre-slaughter muscular scores and the proportion of high-value cuts in the carcass (r 5 0.31) was higher than that obtained by Herring et al (1994) using eight cuts from the carcass compared with three cuts in the present study. The lack of a relationship between live animal muscular scores and the proportion of high-value cuts in meat indicates that, when bone and fat are excluded, there is no effect of muscular score on the distribution of meat in the carcass.…”
Section: Assessorscontrasting
confidence: 80%
“…Skeletal scores taken pre-slaughter showed a positive relationship (r 5 0.22 to 0.52) with the three indicators of fat (carcass fat proportion, carcass fat score and perinephric and retroperitoneal fat) and a negative relationship (r 5 20.18 to 20.38) with carcass meat proportion, proportion of high-value cuts in the carcass, carcass conformation score and carcass value. Other studies (Bailey et al, 1986;Herring et al, 1994) have also shown low negative correlations between various skeletal measurements and percentage carcass lean or retail product.…”
Section: Assessorsmentioning
confidence: 90%
See 1 more Smart Citation
“…Machine classification is deemed preferable to visual assessment because of greater consistency, and producers can have more confidence in the objectivity of the results (Allen, 2007). Several studies quantified the associations of ultrasound (Faulkner et al, 1990;Herring et al, 1994;Hamlin et al, 1995) and live animal scores (Perry et al, 1993a and1993b) with carcass traits. However, few studies have examined the relationship between EU carcass classification scores and carcass composition (Drennan et al, 2008;Conroy et al, 2009a and2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate prediction of carcass value or quality based on body composition would enable early selection of efficient animals by beef producers as well as seed-stock breeders. A subset of the data from this study was used to describe the effectiveness of objective live measurements equations for the prediction of carcass traits (Afolayan et al, 2002a), as opposed to the combination of objective and subjective measurements used in other studies (Perry et al, 1993a and b;Herring et al, 1994). Objective live animal measurements involved simple adoptable techniques that would reduce production costs and allow wider application by the producers.…”
Section: Introductionmentioning
confidence: 99%